Vitamin D aggravates breast cancer by inducing immunosuppression in the tumor bearing mouse. (1st June 2018) - Cao, Yu; Du, Yunting; Liu, Fei; Feng, Yonghui; Cheng, Shitong; Guan, Shu; Wang, Yuying; Li, Xiaoying; Li, Bo; Jin, Feng; Lu, Shilong; Wei, Minjie
The aim of this approach is to test the effects and related mechanism of vitamin D (VD) treatment on the outcomes of breast cancer. BALB/c mice were injected with 4T1 breast cancer cell suspension. The test group was treated with VD reagent. The survival and tumor size of mice were observed. The proliferation of 4T1 in vitro was detected by MTS analysis. The changes of immune parameters and microenvironment in mice were evaluated by flow cytometry and real-time RT-PCR. Our results demonstrate that VD administration caused a decline in survival time and raising the volume of tumor, the decreasing numbers of CD3 + CD4 + T, CD3 + CD8 + T and CD4 + T-bet + IFN-γ + Th1 cells and transcriptions of T-bet and IFN-γ, an increasing number of myeloid-derived suppressor cells and transcription of TGF-β . Our data suggest that the routine clinical application of any strategies targeting VD status for breast cancer therapy is deserved serious consideration.